2014
DOI: 10.1111/1759-7714.12069
|View full text |Cite
|
Sign up to set email alerts
|

Giant solitary fibrous tumor of the lung: A case report

Abstract: Keywords AbstractA solitary fibrous tumor arising from the lung parenchyma is rarely described. Here, we present the clinical, imaging, and histological features of a case of a 54-year-old woman with an incidental lung mass of the right lower lobe on a chest radiograph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In addition, Snail protein stability is finely controlled by GSK3b-dependent phosphorylation and ubiquitination. 18 We also found AEC PQ-exposure could decrease the level of GSK-3b, while the level of GSK-3b was increased after silencing LOX and inactivating LOX. We guessed that PQ-induced LOX could indirectly affect Snail by decreasing the expression of GSK-3b; however, the mechanism is unclear.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In addition, Snail protein stability is finely controlled by GSK3b-dependent phosphorylation and ubiquitination. 18 We also found AEC PQ-exposure could decrease the level of GSK-3b, while the level of GSK-3b was increased after silencing LOX and inactivating LOX. We guessed that PQ-induced LOX could indirectly affect Snail by decreasing the expression of GSK-3b; however, the mechanism is unclear.…”
Section: Discussionmentioning
confidence: 57%
“…It also had been shown to carry out intracellular functions beyond extracellular cross-linkage, including cell migration, cell polarity and EMT. 18 Jansen MK demonstrated that the expression of intracellular LOX was up-regulated after the induction of EMT in MDCK II cells. 19 Both the Cu(II) cofactor and the lysyl-tyrosylquinone cofactor are required for the oxidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…28 LOX family proteins also play a role in epithelial mesenchymal transformation, which is believed to affect cell movement, tumour invasion and metastasis. While these post-translational crosslinks are benecial for added stability of the ECM, overexpression and unusual LOX activity also lead to disorders of the connective and brotic tissue, 29 and are reported as being risk factors for diseases including ovarian cancer. 30 Tryptophan tryptophylquinone (TTQ).…”
Section: Quinonesmentioning
confidence: 99%